Hydrogel based on hyaluronic acid microsphere aggregates and uses thereof

KR1020260132373APending Publication Date: 2026-09-02KNU IND COOPERATION FOUND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020250025183
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2026-09-02

Smart Images

  • Figure PAT00001_ABST
    Figure PAT00001_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a hyaluronic acid microsphere aggregate hydrogel, comprising: a first step of mixing and reacting a hyaluronic acid-dopamine conjugate and a crosslinking agent containing a diglycidyl ether group; a second step of forming microspheres using the reaction mixture; and a third step of adding metal ions to the obtained microspheres to form crosslinks, and a hyaluronic acid microsphere aggregate hydrogel prepared thereby. The hyaluronic acid microsphere aggregate hydrogel of the present invention and a drug delivery system or an injectable for extravascular administration containing the same can be used as a minimally invasive delivery means in the medical and pharmaceutical fields, and can be usefully used as a formulation that can improve patient compliance by reducing the frequency of administration through sustained drug release.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a hyaluronic acid microsphere aggregate-based hydrogel and its uses, and more specifically, to a microsphere aggregate gel that acts as a reservoir based on the aggregation phenomenon upon local injection and spreads among cancer cells to exhibit an anticancer effect, and its uses. Background Technology

[0002] Microsphere aggregate gels have recently emerged as potential biotherapeutic materials applicable in the fields of tissue engineering and regenerative medicine. Microsphere aggregate gels exhibit characteristics such as porosity and injectability, and have been reported to be used in cell culture, tissue engineering, and regenerative medicine (Feng et al., 2022). Microsphere aggregate gels possess various unique properties compared to conventional hydrogels, which make them attractive for biomedical applications. First, their small size allows for injection through small needles and catheters, which is advantageous for minimally invasive delivery. Second, physical interactions between particles within the particle system lead to shear thinning that enables injection, and they maintain a solid-like consistency without chemical deformation after injection. Finally, microsphere aggregate gels possess significant porosity due to the spaces between the microspheres. The level of porosity is controlled by the size and packing density of the microsphere aggregate gel (Daly et al., 2020). Microsphere aggregate gels are formed by interconnecting microspheres through covalent or non-covalent bonds. When a microsphere aggregation gel is injected into tissue, it interlocks with one another to support penetration into the tissue through its porous structure. Microspheres can be prepared using various methods such as emulsification, microfluidics, electrospinning, and spray drying, which have different size distributions (Wilson et al., 2022).

[0003] cis -Diaminedichloroplatinum II( cis-diamminedichloroplatinum II (cisplatin) is a platinum-based anticancer agent that is highly effective and broad-spectrum, but dose-limiting toxicity and other serious side effects cannot be ignored. Side effects include nephrotoxicity, gastrointestinal reactions, neurotoxicity, and resistance, which limit its clinical application. Various strategies have been developed to overcome these side effects and improve the therapeutic indicators of cisplatin (Chen et al., 2019). Over the past few decades, various polymeric drug delivery systems, including polymeric micelles, nanoparticles, cryogels, lipids, and polymers, have been developed to reduce side effects (Solomevich et al., 2020; Abedi et al., 2019; Adarsh ​​et al., 2018; Farias et al., 2020; Gotov, Battogtokh, Shin, & Ko, 2018; Lan et al., 2018; Rezaei et al., 2020). Furthermore, combination therapy has been proven to be a powerful method for minimizing recurrence and enhancing therapeutic efficacy (Yang et al., 2022). Cisplatin activates nicotinamide adenine dinucleotide phosphate (NADPH) oxidases (NOXs), thereby activating superoxide anions (O2 ·-It promotes the generation of reactive oxygen species, and the generated reactive oxygen species are converted into hydrogen peroxide (H2O2) by superoxide dismutase (SOD) (Jiang et al., 2021). Calcium peroxide (Ca) and iron sulfate (Fe) were introduced to combine chemodynamic therapy (CDT) with cisplatin chemotherapy (CT). Ca is receiving much attention as a solid oxidizing agent due to its diverse chemical properties. Ca reacts with water to generate H2O2, and the generated H2O2 leads to the Fenton reaction, which reacts with iron ions to produce hydroxyl radicals (·OH) (Xue et al., 2018). H2O2 produced by cisplatin and Ca reacts with iron ions to generate reactive oxygen species (ROS) for CDT therapy, which can induce apoptosis and necrosis in cancer cells. Accumulated ROS induce ferrotosis (Hu et al., 2022). Additionally, catalysis of the tumor lesion site can induce an oxidative stress response, leading to calcium overload; consequently, this can cause calcification in the lesion site and ultimately result in tumor cell death. Calcicoptosis primarily utilizes the maintenance and accumulation of calcium ions within tumor cells to induce a persistent calcium overload, which disrupts tumor cell metabolism and proliferation, causing cells to malfunction and eventually inducing apoptosis (Hu et al., 2022). Prior art literature

[0004] Republic of Korea Patent Publication No. 10-2022-0113856 (Aug. 17, 2022) Republic of Korea Patent Publication No. 10-2022-0025983 (March 4, 2022) The problem to be solved

[0005] The problem that the present invention aims to solve is to provide a formulation that is easy to administer via local injection and exhibits excellent anticancer activity through continuous drug release.

[0006] In previous studies, the inventors of the present invention have developed typical hydrogel formulations based on hyaluronic acid (HA)-dopamine polymers (HD) (Jeong et al., 2022; Kim et al., 2023). When metal ions are added to HD, the metal ions act as crosslinkers to increase the viscoelasticity of the formulation. Additionally, HD forms polydopamine at high pH, ​​which increases the viscoelasticity of the formulation (Hwang et al., 2021). In the present invention, Fe was added to microspheres (HPC MS) prepared by adding poly(ethylene glycol) diglycidyl ether (PEGDE) and cisplatin to an HD-based formulation to induce interactions between the microspheres, and the viscoelasticity of the formulation was increased by the high pH caused by Ca. The microsphere aggregation gel, composed of small microspheres, can spread widely to cancer cells at the target site via local injection, enabling effective drug delivery, and is suitable for local treatment due to its sustained drug release characteristics. In this study, the physicochemical properties and CT / CDT functions of HPC MS / Ca / Fe microsphere aggregation gel were evaluated for anticancer efficacy through in vitro and animal experiments.

[0007] The problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned technical problems will be clearly understood by those skilled in the art to which the present invention belongs from the description below. means of solving the problem

[0008] To achieve the above-mentioned problem, according to one aspect of the present invention, a method for preparing a hyaluronic acid microsphere aggregate hydrogel is provided, comprising: a first step of mixing and reacting a hyaluronic acid-dopamine conjugate and a crosslinking agent containing a diglycidyl ether group; a second step of forming microspheres using the reaction mixture; and a third step of adding metal ions to the obtained microspheres to form crosslinks.

[0009] According to another aspect of the present invention, a hyaluronic acid microsphere aggregate hydrogel prepared by the above-described manufacturing method is provided.

[0010] According to another aspect of the present invention, a drug delivery system or injectable agent comprising the hyaluronic acid microsphere aggregate hydrogel is provided. Effects of the invention

[0011] According to the present invention, it was revealed that a hyaluronic acid microsphere aggregate hydrogel containing cisplatin exhibits high anticancer activity through the synergistic effect of chemotherapy and chemodynamic therapy, and demonstrates high viscoelasticity and shear thinning characteristics, making it possible to administer by injection to the tumor site. Furthermore, it was revealed that the microsphere aggregate gel, composed of small microspheres, was able to penetrate cancer tissue at the target site through local injection to enable effective drug delivery, and could effectively inhibit tumor growth in vivo without systemic toxicity through continuous drug release characteristics at the tumor site.

[0012] Accordingly, the hyaluronic acid microsphere aggregate hydrogel of the present invention and the drug delivery system or extravascular injection containing the same can be used as a minimally invasive delivery means in the medical and pharmaceutical fields, and can be usefully used as a formulation that can improve patient compliance by reducing the frequency of administration through sustained drug release.

[0013] The effects of the present invention are not limited to the effects described above, and should be understood to include all effects that can be inferred from the composition of the invention described in the description of the invention or the claims. Brief explanation of the drawing

[0014] Fig. 1 This is a schematic diagram of an HPC MS / Ca / Fe microsphere aggregation gel formulation for local treatment of breast cancer. Fig. 2 is an FE-SEM image of the HP MS group and the HPC MS group (scale: 10 μm). Fig. 3 The results of particle size analysis show the average diameter (A) and size distribution (B) of the HP MS group and the HPC MS group. Each data point is expressed as mean ± standard deviation, n ≥ 3. Fig. 4 This is an image of the results of a conductivity test to confirm the gelation characteristics of a microsphere aggregation gel formulation. Fig. 5 This is a diagram illustrating the shear stress and viscosity profiles according to deformation tests, vibration tests, shear rate-shear stress and viscosity tests, as well as the rheological analysis results of the HPC MS, HPC MS / Ca, HPC MS / Fe, and HPC MS / Ca / Fe groups. Fig. 6 This is a plot of the absorbance values ​​of the Ca, Ca / Fe, HPC MS / Ca, and HPC MS / Ca / Fe groups as the results of the H2O2 generation ability test of the microsphere composite aggregation gel (each data point is expressed as mean ± standard deviation, n = 3. * p < 0.05, indicated significant difference between groups). Fig. 7 This is a graph of the absorbance values ​​of the Ca / Fe, HPC MS, HPC MS / Ca, and HPC MS / Ca / Fe groups as the results of the hydroxyl radical generation test of the microsphere composite aggregate gel using TMB-based analysis (each data point is expressed as mean ± standard deviation, n = 3. * p < 0.05, indicated significant difference between groups). Fig. 8 Figure 1 represents the results of the iron ion detection test in breast cancer cells (4T1 cells) using Phen Green SK reagent, showing the relative fluorescence intensity values ​​of the control, Fe, HPC MS, HPC MS / Fe, and HPC MS / Ca / Fe groups (each data point is expressed as mean ± standard deviation, n = 3. * p < 0.05, indicated significant difference between groups). Fig. 9 Figure 1 represents the results of a calcium detection test in breast cancer cells (4T1 cells) using Fluo-3 AM fluorescence, showing the relative fluorescence intensity values ​​of the control, Ca, HPC MS, HPC MS / Ca, and HPC MS / Ca / Fe groups (each data point is expressed as mean ± standard deviation, n = 3. * p < 0.05, indicated significant difference between groups). Fig. 10 This is a graph of cell viability at specific concentrations, showing the cell proliferation inhibition efficiency data for the HP MS (A), Ca / Fe (B), HP MS / Ca / Fe (C), HPC MS (D), and HPC MS / Ca / Fe (E) groups using MTS-based analysis (each data point is expressed as mean ± standard deviation, n = 4). Fig. 11 This is a graph showing the relative ROS levels (%) of the control, HP MS, Ca / Fe, HP MS / Ca / Fe, HPC MS, and HPC MS / Ca / Fe groups as a result of the ROS detection test in breast cancer cells (4T1 cells) (each data point is expressed as mean ± standard deviation, n = 3. * p < 0.05, indicated significant difference between groups). Fig. 12This is a graph showing the relative lipid ROS levels of the control, Fe, Ca / Fe, HPC MS, HPC MS / Fe, and HPC MS / Ca / Fe groups as a result of lipid peroxidation analysis in breast cancer cells (4T1 cells) (each data point is expressed as mean ± standard deviation, n = 3. * p < 0.05, indicated significant difference between groups). Fig. 13 These are the CT imaging test results in a 4T1 tumor-grafted mouse model, showing 3D images and 2D results of a standard hydrogel (HD / PEGDE / cisplatin / Ca / Fe) and a microsphere aggregate hydrogel (HPC MS / Ca / Fe) (pre-injection into the tumor, 10 minutes after injection, and 30 minutes after injection). Fig. 14 Figure 2 represents the results of an in vivo efficacy test for preventing recurrence in a 4T1 breast cancer transplant mouse model, showing the tumor growth curve and excised tumor weight values ​​measured on the final day after local administration of the microsphere aggregate hydrogel (each data point is expressed as mean ± standard deviation, n = 3-6. * p < 0.05, indicated significant difference between groups). Specific details for implementing the invention

[0015] The present invention provides a method for preparing a hyaluronic acid microsphere aggregate hydrogel, comprising: a first step of mixing and reacting a hyaluronic acid-dopamine conjugate and a crosslinking agent containing a diglycidyl ether group; a second step of forming microspheres using the reaction mixture; and a third step of adding metal ions to the obtained microspheres to form crosslinks.

[0016] The mechanism for forming a network of chemical structures in the hyaluronic acid microsphere aggregate hydrogel of the present invention is shown in Fig. 1. The hyaluronic acid-dopamine conjugate is cross-linked between chains by a crosslinking agent containing a diglycidyl ether group, and cisplatin is introduced at this time. After forming this into microspheres, Ca and Fe are added, and the viscoelasticity of the microsphere aggregate gel formulation is increased by the coordination bonding between catechol groups on the surface of the microspheres and iron ions, and by the formation of polydopamine due to the high pH caused by Ca.

[0017] The hyaluronic acid microsphere aggregate hydrogel of the present invention is designed to act as a drug reservoir based on the aggregation phenomenon when locally injected into breast cancer, and to penetrate into the cancer tissue, thereby exhibiting an enhanced anticancer effect through the combined effect of CT by cisplatin and CDT / ferotosis / calcicoptosis by metal ions.

[0018] The method for preparing a hyaluronic acid microsphere aggregate hydrogel of the present invention comprises a step [i.e., a first step] of mixing and reacting a hyaluronic acid-dopamine conjugate with a crosslinking agent containing a diglycidyl ether group. In the first step, the hyaluronic acid-dopamine conjugate can be prepared by an amide bonding reaction using EDC-NHS coupling of hyaluronic acid and dopamine. In summary, hyaluronic acid is dispersed in water, and then the hyaluronic acid dispersion is mixed with an organic solvent solution of EDC and NHS to activate the carboxylic acid groups of the hyaluronic acid. The pH of the mixture is acidified, and then a dopamine solution is added and reacted to obtain a hyaluronic acid-dopamine conjugate.

[0019] The hyaluronic acid included in the above hyaluronic acid-dopamine conjugate may be hyaluronic acid commonly used in the technical field to which the present invention belongs, preferably having an average molecular weight of 10 to 8000 kDa, and more preferably being a low molecular weight grade hyaluronic acid with a molecular weight of 100 to 1000 kDa.

[0020] In one embodiment, the hyaluronic acid and dopamine included in the hyaluronic acid-dopamine conjugate may be included in a weight ratio of hyaluronic acid to dopamine of 50 to 5:1, preferably 25 to 8:1.

[0021] The crosslinking agent used in the method for preparing the hyaluronic acid microsphere aggregate hydrogel of the present invention may be used without limitation as long as it is a material containing a diglycidyl ether group and capable of forming a covalent ether bond by reacting with the hydroxyl group of hyaluronic acid through an epoxy group. Through this crosslinking, the hyaluronic acid structure forms a chemical structure that binds to both ends of the crosslinking agent.

[0022] Examples of crosslinking agents that can be used in the present invention include polyethylene glycol diglycidyl ether (PEGDE), 1,4-butanediol diglycidyl ether, 1,2-ethanediol diglycidyl ether, pentaerythritol tetraglycidyl ether, 1,2-bis(2,3-epoxypropoxy)ethylene, 1,2,7,8-diepoxyoctane, and phenylene-bis-(ethyl)-carbodiimide. 1,6-hexamethylenebis(ethylcarbodiimide), adipic dihydrazide, bis(sulfosuccinimidyl)suberate, hexamethylenediamine, 1-(2,3-epoxypropyl)-2,3-epoxycyclohexane, divinyl sulfone, glutaraldehyde, cyanogen bromide, octenylsuccinic anhydride, acid chloride, methacrylic anhydride, and sodium periodate or a combination thereof, but not limited thereto.

[0023] When using crosslinking agents, the crosslinking ratio with hyaluronic acid can be controlled to suit the intended use of the formed hydrogel, and the degree of crosslinking can be adjusted to maximize the inclusion of the substance introduced (encapsulated) into the crosslinked structure. In alkaline conditions, the epoxy groups of substances containing diglycidyl ether groups preferentially react with the hydroxyl groups (primary alcohols) of hyaluronic acid to form ether bonds, which are known to be more stable than ester or amide bonds. However, a high degree of crosslinking increases rigidity and reduces the feasibility of injection through a syringe needle. Therefore, it is important to design the degree of crosslinking to ensure appropriate rheological properties suitable for extravascular injection and a suitable amount of encapsulated drug. To achieve the above objective, in one embodiment of the present invention, the hyaluronic acid-dopamine conjugate and the crosslinking agent containing a diglycidyl ether group may be mixed and used in a weight ratio of 2 to 100:1, preferably in a weight ratio of 5 to 50:1, and more preferably in a weight ratio of 8 to 20:1.

[0024] In one embodiment of the present invention, a drug to be introduced in the first step may be additionally mixed. For example, a drug requiring local administration, such as an anticancer agent, may be introduced. In an embodiment of the present invention, cisplatin is mixed together to form a structure in which cisplatin is encapsulated in a hyaluronic acid-dopamine conjugate / crosslinker. In this case, the hyaluronic acid-dopamine conjugate and cisplatin may be mixed in a weight ratio of 2 to 1000:1, preferably 10 to 500:1, and more preferably 50 to 200:1.

[0025] The method for preparing a hyaluronic acid microsphere aggregate hydrogel according to the present invention includes a step of forming microspheres using the reactants of the first step [i.e., the second step]. The method used to form microspheres in the second step may be any microsphere manufacturing method commonly used in the art without limitation. For example, it may be one method selected from the group consisting of emulsification, microfluidic methods, electrospinning, and spray drying, but is not limited thereto. For example, if performed by a spray drying process, the unreacted crosslinking agent remaining after the spray drying process can be removed by washing, etc., and microspheres of the hyaluronic acid-dopamine conjugate can be obtained. The microspheres obtained by such a method may have an average diameter of 0.1 to 50 μm, preferably 0.5 to 20 μm, and more preferably 1 to 5 μm.

[0026] The method for preparing a hyaluronic acid microsphere aggregate hydrogel of the present invention comprises a step [i.e., a third step] of adding metal ions to the microspheres obtained in the second step to form cross-links. The metal ions used in the third step may be iron ions, calcium ions, zinc ions, manganese ions, selenium ions, gold ions, silver ions, copper ions, cobalt ions, vanadium ions, titanium ions, cerium ions, chromium ions, ruthenium ions, tungsten ions, or molybdenum ions. The metal ions are formed by the microspheres and the metal salts, respectively (e.g., calcium peroxide (Ca) or iron sulfate (Fe)). It can be mixed in a weight ratio of 1 to 100:1, preferably in a weight ratio of 2 to 50:1, and more preferably in a weight ratio of 5 to 20:1.

[0027] The present invention also provides a hyaluronic acid microsphere aggregate hydrogel prepared by the above-described manufacturing method. The hyaluronic acid microsphere aggregate hydrogel prepared as described above has the characteristic of increased viscoelasticity, formed by aggregation through crosslinking with added microspheres having an average diameter of μm.

[0028] The present invention also provides a drug delivery system or an injectable for extravascular administration comprising the hyaluronic acid microsphere aggregate hydrogel. In order to be used as an injectable for extravascular administration, it must take the form of a hydrogel while simultaneously possessing physicochemical and rheological properties sufficient to be injected from a syringe needle. Since the hydrogel formulation of the present invention exhibits shear thinning properties, it can be used as an injectable formulation for extravascular administration of a drug, and since it exhibits sustained-release properties, it can be safely and efficiently applied to local cancer treatment.

[0030] The present invention will be explained in more detail below through examples. However, the following examples are intended to illustrate the present invention and do not limit the scope of the present invention.

[0032] <Example>

[0033] 1. Experiment

[0034] 1.1. Materials

[0035] HA (M w: ~500 kDa) was purchased from Bioland (Bioland Co., Ltd, Cheonan, South Korea). Cisplatin, N-hydroxysuccinimide (NHS), N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC), Ca, Fe, hyaluronidase, PEGDE, and salt buffer (Hanks' balanced salt solution, HBSS) were purchased from Sigma-Aldrich (Saint Louis, MO, USA). Dopamine (3-hydroxytyramine hydrochloride) was purchased from Tokyo Chemical Industry Co. Ltd (Tokyo, Japan). Penicillin-streptomycin and trypsin-EDTA solution were purchased from Gibco Life Technologies, Inc. (Carlsbad, CA, USA). Phosphate buffered saline (PBS), Dulbecco's phosphate buffered saline (DPBS), fetal bovine serum (FBS), and RPMI 1640 (containing 300 mg / L of L-glutamine and 25 mM NaHCO3) cell culture medium were purchased from Welgene Inc. (Gyeongsan, Republic of Korea). All other materials were of analytical grade.

[0037] 1.2. Synthesis and Analysis of HD Conjugates

[0038] HD polymer conjugates were synthesized using amide bonds of HA and dopamine in the presence of EDC / NHS (Jeong et al., 2022). HA (96 mg) was dissolved in 10 mL of distilled water (DW) and mixed with a solution of EDC (61.3 mg) and NHS (36.8 mg) dissolved in 10 mL of dimethyl sulfoxide (DMSO). To adjust the pH, an HCl solution was added to the mixture to bring the pH value to 5. Dopamine (49.3 mg) dissolved in DMSO (5 mL) was added to the mixture, and the reaction was carried out by stirring at room temperature for 24 hours under light protection. The mixture was placed in a dialysis membrane (molecular weight cut-off (MWCO): 7 kDa) and dialyzed against DW for 3 days to remove unreacted materials other than the HD conjugate. The dialyzed product was freeze-dried.

[0040] 1.3. Preparation and Characteristics of Microsphere Aggregation Gel Formulation

[0041] The HPC MS formulation was prepared by the spray drying method. HD and cisplatin were dissolved separately in distilled water and mixed using a stirrer. After mixing, PEGDE was added to achieve a final concentration of 2.5 / 0.25 / 0.025 mg / mL (HD / PEGDE / cisplatin). To bind HD and PEGDE, the HD / cisplatin mixture was stirred for 2 hours after the addition of PEGDE.

[0042] A mini spray dryer (B-290, BUCHI) was set to 100% suction, 18% pump speed, an internal temperature of 120 ℃, and an external temperature of 60 ℃. The microspheres obtained through spray drying were washed three times with ethanol to remove unreacted PEGDE and then dried at room temperature. The dried microspheres were observed using a field emission-scanning electron microscope (FE-SEM; JSM-7900F, JEOL, Japan). Additionally, after dispersing the microspheres in ethanol, their size was analyzed using particle size analyzers, specifically the ELS-Z1000 (Otsuka Electronics Co. Ltd., Tokyo, Japan) and the Mastersizer 3000 (Malvern Panalytical Ltd, Malvern, UK).

[0043] HPC MS / Ca / Fe The formulation was prepared by a simple mixing method (Yang et al., 2020). HPC MS and Ca were dispersed and dissolved in DW, respectively, and Fe was dissolved in DW, and then mixed by vortexing to achieve a final concentration (mg / mL) ratio of 40:4:4 (HPC MS:Ca:Fe).

[0044] To compare the gelation characteristics of the formulations according to the presence or absence of HPC MS and each crosslinker and pH, the formulations were inverted vertically after a certain period of time and observed visually (Lee et al., 2023). HPC MS (40 mg / mL), HPC MS / Ca (40 / 4 mg / mL), HPC MS / Fe (40 / 4 mg / mL), HPC MS / Ca / Fe (40 / 4 / 4 mg / mL), and HPC MS / Ca / Fe [pH 6] (40 / 4 / 4 mg / mL) samples were each prepared in plastic tubes and reacted at room temperature for 4 hours, after which the tubes were inverted to check.

[0045] To evaluate the rheological properties of the HPC MS / Ca / Fe formulation, a rheometer (MCR 302, Anton Paar GmbH, Graz, Austria) was used. The G′ and G″ values ​​of HPC MS (40 mg / mL), HPC MS / Ca (40 / 4 mg / mL), HPC MS / Fe (40 / 4 mg / mL), and HPC MS / Ca / Fe (40 / 4 / 4 mg / mL) samples, cured for 1 hour after preparation, were measured via amplitude control tests at a frequency of 10 rad / s and a strain range of 1–402%, and via frequency control tests at a frequency of 1–100 rad / s and a strain range of 10%. Shear stress and viscosity tests according to shear rate were conducted at 0.1–100 s -1 It was measured within the shear rate range.

[0046] Hydroxyl radical generation activity was confirmed by 3,3',5,5'-tetramethylbenzidine (TMB) analysis (Kim et al., 2021). An aliquot (0.4 mL) of each sample was placed in a dialysis membrane (MWCO: 12-14 kDa) and cured at room temperature for 4 hours. Afterward, it was placed in a container containing DW (2.5 mL) and reacted at 37 °C for 1 hour. TMB (5 mM, 2.5 mL) was added, and aliquots (0.2 mL) were withdrawn at 0, 15, 30, and 60 minutes, and measured at a wavelength of 650 nm using a spectrometer (SpectraMax i3, Molecular Devices, Sunnyvale, CA, USA).

[0047] In addition, H2O2 production by Ca was evaluated through experiments based on TiOSO4. An aliquot (0.2 mL) of each sample was placed in a dialysis membrane (MWCO: 12-14 kDA) and cured at room temperature for 4 hours. Afterward, it was placed in a container filled with PBS (pH 5.5, 2 mL) and reacted at 37 °C for 30 minutes. After adding TiOSO4 (30 mM, 2 mL) and reacting for 30 minutes, an aliquot (0.2 mL) was obtained from each sample and measured using a spectrometer at a wavelength of 405 nm.

[0048] To confirm the release pattern of calcium ions from the HPC MS / Ca / Fe formulation, the tendency for intracellular accumulation following calcium ion release in breast cancer cells was evaluated (Zhao et al., 2021). 4T1 cells (American Type Culture Collection; Manassas, VA, USA) were placed in 12-well plates at a density of 1.5 × 10⁶ per well. 5 Cells were placed in a 37°C, 5% CO2 incubator for 24 hours. 0.1 mL of the Ca (0.2 mg / mL), HPC MS (2 mg / mL), HPC MS / Ca (2 / 0.2 mg / mL), and HPC MS / Ca / Fe (2 / 0.2 / 0.2 mg / mL) samples were added to the Transwell inserts. After insertion into a 12-well plate, 0.4 mL of cell culture medium was filled into the Transwell inserts and 1.5 mL was filled outside. After treating the cells with the samples, they were incubated for an additional 24 hours under the same conditions. The Transwell inserts were removed from each treatment group and washed with DPBS (pH 7.4). All groups, including the control group, were treated with 5 μM of Fluo-3AM and incubated for 30 minutes under the same conditions. After 30 minutes of treatment, the cells obtained by washing twice with DPBS (pH 7.4) and centrifugation were dispersed in DPBS (pH 7.4) containing 2% FBS and FACSVerse TMIt was analyzed using the system (Becton Dickinson Biosciences).

[0049] To confirm the release pattern of iron ions from the HPC MS / Ca / Fe formulation, the tendency for iron ion accumulation in breast cancer cells was evaluated (Jeong et al., 2022). 4T1 cells were deposited in a 12-well plate at a density of 1.5 × 10⁶ per well. 5 Cells were inserted and cultured for 24 hours in a 37°C, 5% CO2 incubator. 0.1 mL of the samples Fe (0.2 mg / mL), HPC MS (2 mg / mL), HPC MS / Fe (2 / 0.2 mg / mL), and HPC MS / Ca / Fe (2 / 0.2 / 0.2 mg / mL) were added to the Transwell inserts. After insertion into a 12-well plate, 0.4 mL of cell culture medium was filled into the inside of the Transwell insert and 1.5 mL into the outside. After treating the cells with the samples, they were cultured for an additional 24 hours in an incubator under the same conditions. The Transwell inserts for each treatment group were removed and washed with DPBS (pH 7.4). All groups, including the control group, were treated with 5 μM of PhenGreen SK reagent (Phen Green™ SK, Diacetate, P14313, Thermo Fisher Scientific) and cultured for 30 minutes in an incubator under the same conditions. After 30 minutes of treatment, the cells obtained by centrifugation were washed three times with HBSS and dispersed in DPBS (pH 7.4) containing 2% FBS, followed by FACSVerse TM It was analyzed using a system.

[0051] 1.4. Anticancer Efficacy Test in Cancer Cell Lines

[0052] The anticancer activity of HPC MS / Ca / Fe in cancer cell lines was evaluated as its antiproliferative efficacy against 4T1 cells. 4T1 cells were placed in a 96-well plate at a density of 5.0 × 10⁴ per well. 3Two cells were added and cultured in a 37°C, 5% CO2 incubator for 24 hours. HP MS (2000, 1000, 500, 250, 100, 50 μg / mL), Ca / Fe (200 / 200, 100 / 100, 50 / 50, 25 / 25, 10 / 10, 5 / 5 μg / mL), HP MS / Ca / Fe (2000 / 200 / 200, 1000 / 100 / 100, 500 / 50 / 50, 250 / 25 / 25, 100 / 10 / 10, 50 / 5 / 5 μg / mL), HPC MS (2000, 1000, 500, 250, 100, 50 μg / mL) and HPC MS / Ca / Fe (2000 / 200 / 200, 1000 / 100 / 100, Cells were treated with samples (500 / 50 / 50, 250 / 25 / 25, 100 / 10 / 10, 50 / 5 / 5 μg / mL) and cultured for an additional 24 hours in an incubator under the same conditions. Cell Titer 96 for each treatment group ® Aqueous One Solution Cell Proliferation Assay Reagent (Promega Corp., Fitchburg, WI, USA) was applied according to the procedure specified by the manufacturer. 1 hour and 30 minutes after treatment, 100 μL of the supernatant was transferred to a new plate, and the absorbance values ​​for each group were measured at a wavelength of 490 nm using a spectrometer. The cell viability (%) was calculated by comparing the absorbance values ​​with those of the control group.

[0053] The cytotoxicity of HPC MS / Ca / Fe against cancer cell lines was evaluated by detecting intracellular reactive oxygen species (ROS). 4T1 cells were placed in a 12-well plate at a density of 1.5 × 10⁴ per well. 5 Cells were added and cultured for 24 hours in a 5% CO2 incubator maintained at 37°C. HP MS (1 mg / mL), Ca / Fe, including the control group Cells were treated with samples of (0.1 / 0.1 mg / mL), HP MS / Ca / Fe (1 / 0.1 / 0.1 mg / mL), HPC MS (1 mg / mL), and HPC MS / Ca / Fe (1 / 0.1 / 0.1 mg / mL) and incubated in an incubator for an additional 6 hours. Subsequently, cells were treated with a DBPS solution containing carboxy-H2DCFDA (10 μM) and incubated in an incubator for 30 minutes. After 30 minutes of treatment, the cells obtained by washing twice with DPBS and centrifugation were dispersed in DPBS (pH 7.4) containing 2% FBS, followed by FACSVerse TM It was analyzed using a system.

[0054] Lipid peroxidation reaction of HPC MS / Ca / Fe in cancer cell lines is C11-BODIPY 581 / 591 cast It was evaluated using (Lee et al., 2022). 4T1 cells were placed in a 12-well plate at a density of 1.0 × 10⁶ per well. 5 Cells were added and cultured for 24 hours in a 5% CO2 incubator maintained at 37°C. Fe (0.5 mg / mL), Ca / Fe, including the control group Cells were treated with samples of (0.5 / 0.5 mg / mL), HPC MS (5 mg / mL), HPC MS / Fe (5 / 0.5 / 0.5 mg / mL), and HPC MS / Ca / Fe (5 / 0.5 / 0.5 mg / mL) and cultured in an incubator for an additional 24 hours. Subsequently, C11-BODIPY 581 / 591 The cells were treated according to the manufacturer's protocol and cultured in an incubator for 30 minutes. After 30 minutes of treatment, the cells obtained by washing twice with DPBS and centrifugation were dispersed in DPBS (pH 7.4) containing 2% FBS, followed by FACSVerse TM It was observed as a system.

[0056] 1.5. Anticancer Efficacy Test

[0057] The distribution pattern of the prepared HPC MS / Ca / Fe microsphere aggregation gel formulation after local injection was evaluated in a mouse model transplanted with 4T1 tumors. After culturing 4T1 cells, they were suspended in cell culture medium (3 × 10⁶ 5 Cells, 0.05 mL) were inoculated subcutaneously into the mammary gland of female BALB / c mice (average body weight 20 g, Orient Bio, Seongnam, Korea). Tumor volume (V, mm²) 3 ) was calculated according to the following formula.

[0058] V = (4π / 3) × (diameter of major axis / 2) × (diameter of minor axis / 2) × (height / 2) (Faustino-Rocha et al., 2013)

[0059] The distribution pattern of the gel formulations was captured using a 3D micro CT imaging device (Quantum GX2 MicroCT, PerkinElmer, Waltham, MA, USA), with an X-ray voltage of 90 kV, an X-ray current of 88 μA, a scan time of 2 minutes, and a pixel size of 90 μm. A standard hydrogel formulation (HD / PEGDE / cisplatin / Ca / Fe) and a microsphere aggregation gel formulation (HPC MS / Ca / Fe) were each injected around the tumor tissue at a dose of approximately 2.5 mL / kg into a mouse model implanted with a 4T1 tumor.

[0060] The anticancer efficacy of the prepared HPC MS / Ca / Fe microsphere aggregation gel formulation was evaluated in a mouse model implanted with 4T1 tumors. When the tumor thickness reached approximately 7-8 mm after inoculation, the tumor tissue was resected, leaving only a 1-2 mm thick layer. Subsequently, HPC MS / Ca / Fe (40 / 4 / 4 mg / mL) was administered at a dose of 5 mL / kg. Tumor volume was measured on days 0, 3, 5, 7, 10, 12, 14, 17, 19, 21, and 24 after injection, and the weight of the resected tumor was measured on the final day of the experiment.

[0062] 1.6. Data Analysis

[0063] In order to determine whether there were statistically significant differences between each group in the obtained experimental results, the students t -Test (Student's t The metric test and analysis of variance were used. Each experiment was repeated at least three times, and the results were expressed as mean ± standard deviation.

[0065] 2. Results

[0066] 2.1. Synthesis and Analysis of HA Conjugates

[0067] In this invention, HD microspheres encapsulated with cisplatin were prepared and aggregated with Ca and Fe to form a gel formulation, which was then locally administered to tumor tissue to induce CT / CDT / ferotosis / calcicoptosis (Fig. 1). The HD conjugate used for microsphere preparation was synthesized by forming amide bonds between the carboxyl group of HA and the amino group of dopamine via the EDC / NHS crosslinking method. The reaction between HD and PEGDE is based on the formation of crosslinks between HD chains through the binding of the hydroxyl group of HA and the epoxy group of PEGDE (Zerbinati et al., 2021). Analysis of the microspheres prepared by the spray-drying method using FE-SEM confirmed that they were smooth spheres (Fig. 2). HPC MS analysis using the ELS-Z1000 and Mastersizer revealed diameters of 1.44 μm and 1.49 μm, respectively, showing almost no difference depending on the analytical instrument (Fig. 3). There was no significant difference in the size and shape of the microspheres depending on the presence or absence of the drug. Microspheres with a diameter of approximately 1.5 μm were expected to easily penetrate into tumor tissue.

[0069] 2.2. Preparation and Physicochemical Evaluation of Microsphere Aggregation Gel Formulations

[0070] To confirm the increase in viscoelasticity caused by the crosslinking agent in the prepared microsphere aggregation gel formulations, samples were prepared and then inverted vertically to visually observe flowability (Fig. 4). HPC MS and HPC MS / Fe flowed downwards due to low viscoelasticity in the inverted position, whereas the HPC MS / Ca group showed a slight increase in viscoelasticity, as microspheres bound to the upper wall of the tube were visually identifiable. HPC MS / Ca / Fe did not flow downwards even in the inverted position due to increased viscoelasticity resulting from the combined effect of Ca and Fe. It is presumed that the crosslinking characteristic through the coordination bonding between dopamine and iron ions in the microspheres, combined with the high pH caused by Ca, forms polydopamine, thereby increasing the viscoelasticity of the microsphere aggregation gel formulations.

[0071] Rheological analysis was performed to confirm the viscoelastic properties of the prepared microsphere aggregation gel formulation (Fig. 5). For the rheological analysis, deformation tests, vibration tests, and shear rate-shear stress and viscosity tests were conducted. In the deformation test, the cross-deformation points of the HPC MS / Ca and HPC MS / Ca / Fe microsphere aggregation gel groups were approximately 50% and 32%, respectively; the storage modulus (G′), which represents solid properties, was higher than the loss modulus (G″), which represents fluid properties, within the range of the cross-deformation point. In the vibration test as well, the G′ value was higher than the G″ value in the group with added crosslinker. This indicates that the prepared microsphere aggregation gel formulation possesses high elasticity compared to the HPC MS group. Furthermore, in the shear rate-shear stress and viscosity tests, it was confirmed that the viscosity decreased with increasing shear rate in the group with added crosslinker. This indicates a shear thinning characteristic, meaning that the microsphere aggregation gel formulation has high injectability.

[0072] The H2O2 generation capacity of the HPC MS / Ca / Fe microsphere aggregation gel was evaluated by TiOSO4 analysis (Fig. 6). Ca reacts with DW to generate H2O2, while Fe converts H2O2 into hydroxyl radicals through the Fenton reaction. TiOSO4 reacts with H2O2 to develop a color change from colorless to yellow. The Ca and HPC MS / Ca groups exhibited high absorbance due to the H2O2 generated by Ca, whereas the Fe-added Ca / Fe and HPC MS / Ca / Fe groups showed low absorbance as H2O2 was consumed by the Fenton reaction.

[0073] The OH radical generating ability of the HPC MS / Ca / Fe microsphere aggregation gel was measured to evaluate CDT function (Fig. 7). TMB changes from colorless to blue as it is oxidized by hydroxyl radicals. Absorbance values ​​increased over time in all groups except the HPC MS monogroup. Higher absorbance values ​​were observed in HPC MS / Ca and HPC MS / Ca / Fe compared to the HPC MS monogroup. All these results demonstrate the successful hydroxyl radical generating ability of the HPC MS / Ca / Fe microsphere aggregation gel and are expected to enable CDT therapy for cancer.

[0074] To confirm the pattern of iron ion release from the prepared microsphere aggregation gel formulation, the intensity of the fluorescence of the Phen Green SK reagent reacting with iron ions accumulating in breast cancer cells (4T1 cells) treated with the sample was evaluated using a flow cytometer (Fig. 8). When the diacetate group of Phen Green SK detaches from the cell and reacts with iron ions, the intensity of the fluorescence decreases. Excluding the control group and the HPC MS group that did not contain iron ions, the groups containing Fe showed a decrease in fluorescence intensity, indicating that iron ions are released from the microsphere aggregation gel and accumulate inside the cell.

[0075] To confirm the calcium ion release pattern from the prepared microsphere aggregation gel formulation, breast cancer cells (4T1 cells) were treated with the sample, and the intensity of Fluo-3 AM fluorescence reacting with calcium ions accumulating in the cells was evaluated using a flow cytometer (Fig. 9). Fluo-3 AM binds to calcium ions within the cell and emits green fluorescence. The high fluorescence values ​​observed in all groups except the control group indicate that calcium ions are released from the microsphere aggregation gel and accumulate inside the cells. Since cisplatin has been reported to increase the accumulation of calcium ions from the extracellular to the intracellular environment, it appears that the HPC MS group also exhibited high fluorescence values ​​(Gokce et al., 2019).

[0077] 2.3. Evaluation of Anticancer Efficacy in Cancer Cell Lines

[0078] To evaluate the anticancer activity of the prepared HPC MS / Ca / Fe microsphere aggregation gel, antiproliferative efficacy tests using MTS reagents, intracellular reactive oxygen species analysis, and lipid peroxidation reaction evaluation analyses were conducted in breast cancer cell lines (4T1 cells). In the antiproliferative test (Fig. 10), no significant antiproliferative efficacy was observed in the HP MS group, whereas cytotoxicity was observed in the Ca / Fe group at 200 / 200 μg / mL. Furthermore, cytotoxicity appeared stepwise in the HPC MS and HPC MS / Ca / Fe groups as the concentration increased, and the HPC MS / Ca / Fe group showed higher cytotoxicity than the HPC MS group. This is based on the induction effects of ferrotosis and calcicoptosis by cisplatin and metal ions.

[0079] To evaluate the anticancer activity of the HPC MS / Ca / Fe microsphere aggregation gel, intracellular ROS (e.g., H2O2) levels were quantified by fluorescence intensity (Fig. 11). While ROS levels were low in the control and HP MS groups, high ROS levels were measured in the Ca / Fe, HP MS / Ca / Fe, HPC MS, and HPC MS / Ca / Fe groups. In particular, the HPC MS / Ca / Fe group showed significantly higher ROS levels compared to the other groups. These high ROS levels lead to apoptosis, and it can be seen that the HPC MS / Ca / Fe group exhibited the greatest anticancer activity against breast cancer cells (4T1 cells).

[0080] Lipid peroxidation reactions were analyzed to evaluate the ferrotosis-inducing effect of the HPC MS / Ca / Fe microsphere aggregation gel (Fig. 12). Ferrotosis is iron-dependent cell death in which ROS cause lipid peroxidation in the cell lipid membrane, thereby inducing apoptosis. C11-BODIPY 581 / 591 As a lipid analog, it switches from red fluorescence to green fluorescence when oxidized by ROS. Stronger green fluorescence indicates higher lipid peroxidation. The HPC MS / Ca / Fe group exhibited fluorescence values ​​approximately three times higher than the control group, implying that intracellular iron ions released and accumulated in the prepared microsphere aggregation gel caused lipid peroxidation, which can induce perotosis.

[0082] 2.4. Evaluation of Anticancer Efficacy in Experimental Animals

[0083] CT imaging was performed to evaluate the distribution pattern of the microsphere aggregate hydrogel (MAH) prepared in this study after local injection into a mouse model implanted with a 4T1 tumor (Fig. 13). As shown in the 3D images, it was confirmed that the microsphere aggregate hydrogel (HPC MS / Ca / Fe) administration group was widely and uniformly distributed within the tumor tissue compared to the conventional hydrogel formulation (HD / PEGDE / cisplatin / Ca / Fe) administration group. In particular, the 2D image results also confirmed that while the conventional hydrogel formulation (HD / PEGDE / cisplatin / Ca / Fe) administration group was located locally, the microsphere aggregate hydrogel (HPC MS / Ca / Fe) administration group was widely spread across the tumor tissue boundary. These CT imaging results indicate that the developed microsphere aggregate hydrogel (HPC MS / Ca / Fe) formulation is uniformly distributed within the tumor tissue and can penetrate deeply into the tumor tissue.

[0084] To evaluate the efficacy of the prepared HPC MS / Ca / Fe microsphere aggregation gel formulation in preventing tumor recurrence, the sample was injected into a site where a portion of the tumor was left intact in a mouse model implanted with 4T1 breast cancer, and then sutured (Fig. 14). The HPC MS / Ca / Fe group, which showed a synergistic effect with the combined use of cisplatin and CT / CDT of Ca and Fe, exhibited inhibited growth to the extent that the tumor volume was only about 25% of the control group by the end of the experiment ( p In addition, the tumor recurrence prevention efficacy was similar to the tumor volume results, with the resected tumor weight in the HPC MS / Ca / Fe group at the end of the experiment being only about 28% of that of the control group. This means that the HPC MS / Ca / Fe samples successfully released drugs within the cancer cells to induce CT / CDT / ferotosis / calcicoptosis, thereby inhibiting cancer cell growth.

[0086] 3. Conclusion

[0087] In this study, we designed a microsphere aggregation gel that acts as a reservoir based on aggregation phenomena upon local injection into breast cancer, while simultaneously penetrating tumor tissue to exhibit anticancer effects. After penetrating the tumor tissue, the microsphere aggregation gel enhanced anticancer efficacy by combining CT induced by cisplatin released from microspheres with CDT / ferotosis / calcicoptosis induced by metal ions. The HPC MS / Ca / Fe formulation, prepared by cross-linking HD chains via PEGDE, adding cisplatin, and spray-drying, with Ca and Fe added to control viscoelasticity, demonstrated high viscoelasticity and the feasibility of syringe injection. Cisplatin and Ca trigger a Fenton reaction in which they release H2O2, while Fe reacts with H2O2 to generate hydroxyl radicals. In vitro experiments using 4T1 breast cancer cells confirmed that calcium and iron ions released from the HPC MS / Ca / Fe formulation accumulate in cancer cells, inducing ferotosis and calcicoptosis. In addition, it was confirmed that tumor growth was inhibited in animal models inoculated with 4T1 tumors. The HPC MS / Ca / Fe formulation did not exhibit systemic toxicity in animal models, suggesting that it is a biosafe formulation that can be effectively used for the local treatment of breast cancer via CT / CDT / ferotosis / calcicoptosis.

[0089] 4. Summary

[0090] Cisplatin-sutured microspheres based on a hyaluronic acid-dopamine (HD) conjugate were prepared using a spray-drying method. A microsphere aggregation gel formulation was designed by cross-linking the prepared microspheres with calcium peroxide (Ca) and iron sulfate (II, Fe) and used for the local treatment of breast cancer. Ca induces ferrotosis through the Fenton reaction, in which it reacts with water in the cancer cell microenvironment to release hydrogen peroxide (H2O2), while Fe reacts with H2O2 to generate hydroxyl radicals. Additionally, intracellular calcium ions induce calcification of the cell membrane, thereby causing calcicoptosis. High anticancer activity was demonstrated through the synergistic effect of chemotherapy (CT) and chemodynamic therapy (CDT). The microsphere aggregation gel exhibited high viscoelasticity, shear thinning properties, and sustained-release characteristics, and did not cause systemic toxicity in vivo. Furthermore, the microsphere aggregation gel injected into the tumor site effectively inhibited the growth of breast cancer. The microsphere aggregation gel formulation suggests that it can be safely and efficiently applied for local cancer treatment by inhibiting breast cancer growth through local injection.

[0092] 5. References

[0093] Feng, Q., Li, D., Li, Q., Cao, X., Dong, H., 2022. Microgel assembly: Fabrication, characteristics and application in tissue engineering and regenerative medicine. Bioact. Mater. 9, 105-119.

[0094] Daly, AC, Riley, L., Segura, T., Burdick, J.A., 2020. Hydrogel microparticles for biomedical applications. Nat. Rev. Mater. 5(1), 20-43.

[0095] Wilson, K. L., Perez, S. C. L., Naffaa, M. M., Kelly, S. H., Segura, T., 2022. Stoichiometric Post-Modification of Hydrogel Microparticles Dictates Neural Stem Cell Fate in Microporous Annealed Particle Scaffolds. Adv. Mater. 34(33), 2201921.

[0096] Chen, Q., Luo, L., Xue, Y., Han, J., Liu, Y., Zhang, Y., Yin T., Wang L., Cun D., Gou J., He H., Tang, X., 2019. cisplatin-loaded polymeric complex micelles with a modulated drug / copolymer ratio for improved in vivo performance. Acta Biomater. 92, 205-218.

[0097] Solomevich, S. O., Dmitruk, E. I., Bychkovsky, P. M., Nebytov, A. E., Yurkshtovich, T. L., Golub, N. V., 2020. Fabrication of oxidized bacterial cellulose by nitrogen dioxide in chloroform / cyclohexane as a highly loaded drug carrier for sustained release of cisplatin. Carbohydr. Polym. 248, 116745.

[0098] Abedi, M., Abolmaali, S. S., Abedanzadeh, M., Borandeh, S., Samani, S. M., Tamaddon, A. M., 2019. Citric acid functionalized silane coupling versus post-grafting strategy for dual pH and saline responsive delivery of cisplatin by Fe3O4 / carboxyl functionalized mesoporous SiO2hybrid nanoparticles: A-synthesis, physicochemical and biological characterization. Mater. Sci. Eng. C. 104, 109922.

[0099] Adarsh, N. N., Frias, C., Ponnoth Lohidakshan, T. M., Lorenzo, J., Novio, F., Garcia-Pardo, J., Ruiz-Molina, D., 2018. Pt(IV)-based nanoscale coordination polymers: Antitumor activity, cellular uptake and interactions with nuclear DNA. J. Chem. Eng. 340, 94-102.

[0100] Farias, T., Hajizadeh, S., Ye, L., 2020. Cryogels with high cisplatin adsorption capacity: Towards removal of cytotoxic drugs from wastewater. Sep. Purif. Technol. 235, 116203.

[0101] Gotov, O., Battogtokh, G., Shin, D., Ko, Y. T., 2018. Hyaluronic acid-coated cisplatin conjugated gold nanoparticles for combined cancer treatment. J. Ind. Eng. Chem. 65, 236-243.

[0102] Lan, X., She, J., Lin, D., Xu, Y., Li, X., Yang, W., Lui, V. W. Y., Jin, L., Xie, X., Su, Y., 2018. Microneedle-mediated delivery of lipid-coated cisplatin nanoparticles for efficient and safe cancer therapy. ACS Appl. Mater. Interfaces 10(39), 33060-33069.

[0103] Rezaei, S. J. T., Sarijloo, E., Rashidzadeh, H., Zamani, S., Ramazani, A., Hesami, A., Mohammadi, E., 2020. pH-triggered prodrug micelles for cisplatin delivery: Preparation and in Vitro / Vivo evaluation. React. Funct. Polym. 146, 104399.

[0104] Yang, N., Zhang, T., Cao, C., Mao, G., Shao, J., Song, X., Wang, W., Mou, X., Dong, X., 2022. BSA stabilized photothermal-Fenton reactor with cisplatin for chemo / chemodynamic cascade oncotherapy. Nano Res. 15(3), 2235-2243.

[0105] Jiang, Y., Liu, Y., Wang, M., Li, Z., Su, L., Xu, X., Xing, C., Li, J., Lin, L., Lu, C., Yang, H., 2021. siRNA-Based Carrier-Free System for Synergistic Chemo / Chemodynamic / RNAi Therapy of Drug-Resistant Tumors. ACS Appl. Mater. Interfaces 14(1), 361-372.

[0106] Xue, Y., Sui, Q., Brusseau, M. L., Zhou, W., Qiu, Z., Lyu, S., 2019. Insight into CaO2-based Fenton and Fenton-like systems: strategy for CaO2-based oxidation of organic contaminants. J. Chem. Eng. 361, 919-928.

[0107] Hu, H., Xu, Q., Mo, Z., Hu, X., He, Q., Zhang, Z., Xu, Z., 2022. New anti-cancer explorations based on metal ions. J. Nanobiotechnology 20(1), 1-21.

[0108] Jeong, D. I., Kim, S., Lee, S. Y., Kim, H. J., Lee, J., Lee, K., Cho, H. J., 2022. Iron sulfate-reinforced hydrogel reactors with glucose deprivation, serial reactive oxygen species generation, ferroptosis induction, and photothermal ablation for cancer therapy. J. Chem. Eng. 438, 135584.

[0109] Kim, S., Ahn, J. H., Jeong, D. I., Yang, M., Jeong, J. H., Choi, Y. E., Kim, H. J., Han, Y., Karmakar, M., Ko, H. J., Cho, H. J. 2023. Alum-tuned hyaluronic acid-based hydrogel with immune checkpoint inhibition for immunophoto therapy of cancer. J. Control. Release. 362, 1-18.

[0110] Hwang, C., Lee, S. Y., Kim, H. J., Lee, K., Lee, J., Kim, D. D., Cho, H. J., 2021. Polypseudorotaxane and polydopamine linkage-based hyaluronic acid hydrogel network with a single syringe injection for sustained drug delivery. Carbohydr. Polym. 266, 118104.

[0111] Yang, M., Lee, S.Y., Kim, S., Koo, J.S., Seo, J.H., Jeong, D.I., Hwang, C.R., Lee, J., Cho, H.J., 2020. Selenium and dopamine-crosslinked hyaluronic acid hydrogel for chemophotothermal cancer therapy. J. Control. Release 324, 750-764.

[0112] Lee, S. Y., Seo, J. H., Kim, S., Hwang, C., Jeong, D. I., Park, J., Yang, M., Huh, J. W., Cho, H. J., 2023. Cuproptosis-Inducible Chemotherapeutic / Cascade Catalytic Reactor System for Combating with Breast Cancer. Small 2301402.

[0113] Kim, S., Seo, J. H., Jeong, D. I., Yang, M., Lee, S. Y., Lee, J., Cho, H. J., 2021. Fenton-like reaction, glutathione reduction, and photothermal ablation-built-in hydrogels crosslinked by cupric sulfate for loco-regional cancer therapy. Biomater. Sci. 9(3), 847-860.

[0114] Zhao, H., Wang, L., Zeng, K., Li, J., Chen, W., Liu, Y. N., 2021. Nanomessenger-mediated signaling cascade for antitumor immunotherapy. ACS nano 15(8), 13188-13199.

[0115] Lee, S. Y., Park, J., Jeong, D. I., Hwang, C., Lee, J., Lee, K., Cho, H. J., 2022. Ferrocene and glucose oxidase-installed multifunctional hydrogel reactors for local cancer therapy. J. Control. Release. 349, 617-633.

[0116] Faustino-Rocha, A., Oliveira, P. A., Pinho-Oliveira, J., Teixeira-Guedes, C., Soares-Maia, R., Da Costa, R. G., Colaco, B., Pires, M. J., Colaco, J., Ferreira, R., Ginja, M., 2013. Estimation of rat mammary tumor volume using caliper and ultrasonography measurements. Lab. Anim. 42(6), 217-224.

[0117] Zerbinati, N., Sommatis, S., Maccario, C., Capillo, M. C., Grimaldi, G., Alonci, G., Protasoni. M., Rauso. R., Mocchi, R., 2021. Toward physicochemical and rheological characterization of different injectable hyaluronic acid dermal fillers cross-linked with polyethylene glycol diglycidyl ether. Polym., 13(6), 948.

[0118] Gokce Kutuk, S., Gokce, G., Kutuk, M., Gurses Cila, H. E., & Naziroglu, M. (2019). Curcumin enhances cisplatin-induced human laryngeal squamous cancer cell death through activation of TRPM2 channel and mitochondrial oxidative stress. Sci. Rep. 9(1), 17784.

[0120] The foregoing description of the present invention is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without altering the technical spirit or essential features of the present invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. For example, each component described as a single unit may be implemented in a distributed manner, and components described as distributed may likewise be implemented in a combined form.

[0122] The scope of the present invention is defined by the claims set forth below, and all modifications or variations derived from the meaning and scope of the claims and equivalent concepts thereof should be interpreted as being included within the scope of the present invention.

Claims

Claim 1 A method for preparing a hyaluronic acid microsphere aggregate hydrogel, comprising: a first step of mixing and reacting a hyaluronic acid-dopamine conjugate and a crosslinking agent containing a diglycidyl ether group; a second step of forming microspheres using the reaction mixture; and a third step of adding metal ions to the obtained microspheres to form crosslinks. Claim 2 In claim 1, the crosslinking agent containing a diglycidyl ether group comprises polyethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,2-ethanediol diglycidyl ether, pentaerythritol tetraglycidyl ether, 1,2-bis(2,3-epoxypropoxy)ethylene, 1,2,7,8-diepoxyoctane, phenylenebis-(ethyl)-carbodiimide, 1,6-hexamethylenebis(ethylcarbodiimide), adipic acid dihydrazide, bis(sulfosuccinimidyl)suberate, hexamethylenediamine, 1-(2,3-epoxypropyl)-2,3-epoxycyclohexane, divinyl sulfone, glutaraldehyde, cyanogen bromide, octenylsuccinic anhydride, A method for preparing a hyaluronic acid microsphere aggregate hydrogel, wherein the one is selected from the group consisting of acyl chloride, methacrylic anhydride, sodium periodate, and combinations thereof. Claim 3 A method for preparing a hyaluronic acid microsphere aggregate hydrogel according to claim 1, wherein the hyaluronic acid-dopamine conjugate and a crosslinking agent containing a diglycidyl ether group are mixed in a weight ratio of 2 to 100:

1. Claim 4 A method for preparing a hyaluronic acid microsphere aggregate hydrogel according to claim 1, wherein cisplatin is mixed together in the first step. Claim 5 A method for preparing a hyaluronic acid microsphere aggregate hydrogel according to claim 4, wherein the hyaluronic acid-dopamine conjugate and cisplatin are mixed in a weight ratio of 2 to 1000:

1. Claim 6 A method for manufacturing a hyaluronic acid microsphere aggregate hydrogel according to claim 1, wherein the microspheres are manufactured by one method selected from the group consisting of emulsification, microfluidic method, electrospray, and spray drying. Claim 7 A method for preparing a hyaluronic acid microsphere aggregate hydrogel according to claim 1, wherein the microspheres have an average diameter of 0.1 to 50 μm. Claim 8 A method for preparing a hyaluronic acid microsphere aggregate hydrogel according to claim 1, wherein the metal ion is an iron ion or a calcium ion. Claim 9 A method for preparing a hyaluronic acid microsphere aggregate hydrogel according to claim 1, wherein the microspheres and the metal salt are mixed in a weight ratio of 1 to 100:

1. Claim 10 A hyaluronic acid microsphere aggregate hydrogel produced by the manufacturing method of any one of claims 1 to 9. Claim 11 A drug delivery system comprising the hyaluronic acid microsphere aggregate hydrogel of claim 10. Claim 12 An injectable preparation comprising the hyaluronic acid microsphere aggregate hydrogel of claim 10.